Meningkatkan Budaya Bersih dan Sehat serta Manfaatnya pada Usaha Ternak Sapi Perah Rakyat di Jawa Barat - Erwidodo; Ariningsih, Ening; Purwantini, Tri Bastuti; Irawan, Aldho Riski (Analisis Kebijakan Pertanian, 2023)
Improving the quality of fresh milk is still seen as a challenge and, at the same time, a key to the success of the development of smallholder dairy farming. One of the quality measures of fresh milk that determines the price level is TPC, which is directly related to the level of cleanliness of cages, techniques for raising cows, and milking and handling fresh milk. This paper aims to discuss the promotion of 'clean and healthy' smallholder dairy farming practices and its benefits, and how the roles of government, researchers/academics, cooperatives, and the milk processing industry should play in this effort. The data used in this paper is part of the IndoDairy Smallholder Household Resurvey (ISHR) data, which was collected within a research collaboration between ICASEPS and ACIAR. Data was collected in December 2021 through interviews with 410 dairy farmers in Bandung, Garut, Cianjur, and Bogor Regencies. The data and information obtained were analyzed descriptively. The 'clean and healthy' culture among smallholder dairy farmers is still far from best practices and what was expected, but not impossible to improve. For this reason, coordination and cooperation, as well as the active roles of all stakeholders, especially farmers, dairy farmer cooperatives, milk processors, central government, regional governments, and universities, are urgently needed.